Comparative evaluation of photocatalytic performance of hexagonal ferrites procured via sol-gel route. (2019) - Kaur, Paramdeep; Kaushik, Anupama; Singhal, Sonal
Abstract: Of recently, ferrite nanostructures have gained immense interest of scientific community owing to their photocatalytic applications. Out of different types of ferrites, M-type Hexaferrites possess high saturation magnetization and considerably high coercivity with high chemical stability and corrosion resistance. These M-type hexaferrites have not been much explored as photocatalysts. So in this context, in the present work M-type Barium and strontium hexaferrites (MFe12 O19, M=Ba, Sr) have been successfully synthesised by sol-gel auto combustion method. XRD studies confirmed that the samples have single phase M-type hexagonal nanostructure and P63 /mmc space group. Crystallite size was found to increase when annealing temperature was increased from 600 °C to 1000 °C. The FT-IRSpectra confirmed the presence of tetrahedral and octahedral sites in BaFe12 O19 and SrFe12 O19 lattice. The surface morphology of hexagonal ferrites was characterized by FE-SEM images and found to be distorted hexagons. The photocatalytic behaviour of BaFe12 O19 and SrFe12 O19 was evaluated for the degradation of methyl orange under visible light irradiation and it was observed that SrFe12 O19 possessed better photocatalytic activity as compared to BaFe12 O19 due to smaller particle size.